(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Now a days we are looking for alternate sources like electric vehicles, in order to cut down the pollution from automobiles which are growing rapidly. Across the globe, governments have been tackling the concerning problem of air-polluting emissions by committing significant resources to improving air quality. Achieving the goal of air purification will require that both the private and public sectors invest in clean energy technology. It will also need a transition from conventional houses to smart houses and from conventional vehicles to electric vehicles (EVs). It will be necessary to integrate renewable energy sources (RESs) such as solar photovoltaics, wind energy systems and diverse varieties of bioenergies. In this paper, a hybrid converter is proposed and designed to realize the integration of the DC/DC converter, and DC/AC inverter together in the Battery Electric Vehicles (BEVs) power train with high performance in any operating mode, acting as a backup generator to supply emergency power directly to home.